Development of Freshwater Fish Cultivation Business and Its Derivative Products In Kajar Hamlet - Gogor Arif Handiwibowo (IPTEK Journal of Proceedings Series, 2023)
Batu City is well-known as one of the cities based on agribusiness and tourism in Indonesia. Agribusiness that is widely developed in Batu City are vegetables and fruits. Kajar Hamlet which is located in Pandanrejo Village, Bumiaji District, Batu City certainly has great agribusiness potential as well. Kajar Hamlet also owns various forms of agribusiness with vegetable and fruit products as well as decorative flowers. But the potential that is no less interesting is the large demand for fresh freshwater fish products that come from many restaurants. Kelompok Peternak Ikan Nila is trying to develop a tilapia cultivation business. Starting from assistance from ITS-Surabaya (as university) to cultivate tilapia using cages in waterways in Kajar Hamlet and evaluation of failures due to the risk of flash floods that have occurred, tilapia cultivation was made using fish ponds by utilizing the residents' unproductive land and the adequacy of water from existing waterways without changing the main function of the waterways as irrigation for agricultural areas. This paper attempts to present the process of developing a freshwater fish farming business in Kajar Hamlet along with an analysis of the business and potential of derivative products that can be further developed.